Gottebenbildlichkeit und Menschenwürde: neutestamentliche Kontrapunkte zu einer "klassischen Begründungsfigur" theologischer Anthropologie - Rehfeld, Emmanuel L. (Zeitschrift für Theologie und Kirche, 2021)
The Old Testament statement that humanity is created in the image of God is not suited to grounding the increasingly controversial concept of "human dignity." First, the New Testament reception of the claim does not interpret the idea of imago Dei anthropologically, but binds it exclusively to Jesus Christ (2Cor 4:4; Col 1:15) and those who are "in Christ" (cf. Rom 8:29; 1Cor 15:49b; 2Cor 3:18). Second, there are pneumatological reasons to be wary of converting theological statements into political concepts (cf. 1Cor 2:6-16). The secular concept of "human dignity" therefore requires a solid political rationale, which can, however, be appropriated theologically.